النزعة التجريبية وآليات التحديث في رواية ليمة المميار "لغادة السماف" - بوسعد, سميرة (Université de M'sila, 2018)
أضحت مغامرة التجريب تدفع الروائيين العرب، للتجاوز والاختراق، والانزياح عن المألوف السردي فكان البحث المستمر وسيلة بغية التجديد، والبحث عن أشكال فنية جديدة وفق تجربة إبداعية تتخذ التجريب أرضية لها، وهذا ما جعل الرواية تنطلق في أفق رحبة مفتوحة وجامحة. فتفاعلت الروائية السورية "غادة السمان" مع مغامرة التجريب الروائي، واعتمدت تقنيات رواية تيار الوعي، والقائمة في الأصل على الاسترجاع، واستحضار ما مضى بشكل مكثف مما يجعل التراتب الزمني يختل، فتبدو المسترجعات من الذاكرة غير مرتبة منطقيا، ومندفعة باستمرار، مثل سيلان المياه، فتتدفق الأفكار، وهذا باستخدام تقنية المونولوج الداخلي، والتداعي الحر، وفيضان الوعي، لأن الاسترجاع ليس مقصودا إنما يثيره مثير خارجي يجعلها تتدافع، فتبدو الشخصية الروائية شاردة، شبه منومة مغناطسيا، لأنها تعيش حوارا داخليا. تعد ممارسة "غادة السمان" للرواية، ممارسة تحتوي معالم التجريب، حيث أفسح التجريب أمامها، الوعي بشروط الابداع الروائي، فأسفرت أعمالها عن رواية فنية تكشف عن منعطفات روائية جديدة. The adventure of experimentation pushes today Arab novelists to overtake, to pierce and to move away from the usual narration. Indeed, the permanent search was a means for the purpose of renewal and the quest for new artistic forms following a creative experiment based on experimentation which led the novel to hover in vast, open and broad horizons. The Syrian novelist Ghada Samman interacts with the adventure of romance experimentation by adopting novel techniques of the stream of consciousness that is based mainly on the recovery and evocation of what has gone through in an intensive way. This disturbs the temporal succession so that what is recalled from memory becomes logically untidy, and permanently flowing out like the flow of water then the ideas run using the technique of the interior monologue, the free association, and the deluge of consciousness. Indeed, the recall is not intentional but it is stimulated by an external stimulator making them jostle then the novelist personality appears distracted, almost hypnotized because she lives an inner dialogue. GHADA Samman's practice of the novel is a practice that includes the parameters of experimentation. Indeed, the experiment allowed her the conscience to the conditions of the novelistic creation whose works gave rise to an artistic novel revealing new novelistic turns.